1989
DOI: 10.2307/3869001
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated Endocytosis in Plant Cells

Abstract: We have employed fluorescein and 1251-labeled elicitors of the defense response in soybeans to monitor the cellular distribution and movement of elicitors following their addition to a soybean cell suspension culture. Our results indicate that the macromolecular elicitors first bind to the cell surface and then internalize in a temperature-and energy-dependent endocytotic process. Within a few hours, virtually all of the elicitor is concentrated in the major vacuole or tonoplast of the cell. Nonspecific (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 3 publications
1
25
0
Order By: Relevance
“…In addition, the clustering we observe is temperature-dependent (Fig. 2 a and d), as are receptor clustering in animal cells (34) and receptor-mediated endocytosis in plants (36). Although the ABP clusters (-4 ,um; Fig.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, the clustering we observe is temperature-dependent (Fig. 2 a and d), as are receptor clustering in animal cells (34) and receptor-mediated endocytosis in plants (36). Although the ABP clusters (-4 ,um; Fig.…”
Section: Discussionmentioning
confidence: 59%
“…The oxidative burst is an early localized defense response that involves the production of potentially cytotoxic quantities of H 2 O 2 and O 2 (1). Although genes known to be associated with generation of the oxidative burst have not yet been isolated, identification of signaling events leading to this response so far include receptor binding (16), activation of G proteins (17), stimulation of phospholipases C (18) and A (19), and changes in protein phosphorylation (20). Presumably, one or more of these essential signal transduction intermediates could constitute the product of an R gene if it were specifically activated by a corresponding avirulence gene product from an incompatible pathogen.…”
mentioning
confidence: 99%
“…Most commonly used forms of nitrogen labeling involve K 15 NO 3 and 15 NH 4 15 NO 3 in the plant growth medium. The first biological experiments involving 15 N-labeling in plants were carried out on suspension cell cultures [1][2][3]. More recently, successful labeling of whole plants and seedlings in liquid culture has been achieved and a thorough analysis of full versus partial 15 N labeling in Arabidopsis plants has revealed that both methods yield comparable results [4].…”
Section: Introductionmentioning
confidence: 99%
“…The first biological experiments involving 15 N-labeling in plants were carried out on suspension cell cultures [1][2][3]. More recently, successful labeling of whole plants and seedlings in liquid culture has been achieved and a thorough analysis of full versus partial 15 N labeling in Arabidopsis plants has revealed that both methods yield comparable results [4]. A general workflow of the data processing involved in 15 Nlabeling experiments was outlined [5] and most common pitfalls and problems in protein identification in labeling experiments due to an increased number of isobaric amino acids in the fully labeled proteome of Arabidopsis have been described [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation